Experimental investigations and numerical modelling of in-situ reactive caps for PAH contaminated marine sediments - Bortone, Imma; Labianca, Claudia; Todaro, Francesco; De Gisi, S.; Coulon, Frederic; Notarnicola, M. (Elsevier, 2019)
The present study compared numerical modelling and experimental investigations to evaluate the effectiveness of in-situ reactive capping for marine sediments contaminated by polycyclic aromatic hydrocarbons (PAHs). As a case study, sediment samples from Mar Piccolo (Italy) were analyzed and experiments were undertaken using batch columns. Two types of capping amendments were tested: AquaGate® + 5 % of powdered activated carbon (AG PAC) and Organoclay Reactive Core Mat (OC RCM). The column tests were carried out for 20 days, obtaining a short-term PAH distribution for three cases analysed, which compared the application of the two caps with no intervention. In parallel, in order to evaluate the intervention long term efficacy, an ad-hoc multilayered model predicting PAH concentrations into the sediments and the overlying water column was developed and validated with the experimental results. Both capping systems considerably reduced PAH concentrations in the overlying water, with the highest performance seen in AG PAC for benzo[a]pyrene (99 %) and anthracene (72 %); results also confirmed in the model predictions. In addition, the numerical simulations indicated a good efficiency of both caps over time, obtaining PAH values below the threshold limit in the long term. Although further experiments need to be developed accounting for multiple contamination competitiveness.
Keywords: In-situ capping; Marine sediments; Adsorption; Predictive model; PAHs